The Role of Special Differential Treatment for Developing Countries in GATT and the World Trade Organization - Michalopoulos, Constantine (World Bank, Washington, DC, 2014)
The author analyzes how changes in thinking about the role trade plays in economic development have been reflected in provisions affecting developing countries in the GATT and the WTO. He focuses on the provisions calling for the special and differential treatment of developing countries. The WTO's special, and differential treatment has been extended to include measures of technical assistance, and extended transition periods to enable countries to meet their commitments in new areas agreed on in the Uruguay round of negotiations. At the same time, many WTO provisions encourage industrial countries to give developing countries preferential treatment, through a variety of measures, none of them legally enforceable. The author concludes that weaknesses in the institutional capacity of many developing countries, provide a conceptual basis for continuing special, and differential treatment in the WTO, but that the benefits should be targeted only to low-income developing countries, and those that need help becoming integrated with the international trading system. In addition, an effective system of graduation, should be put in place for higher-income developing countries. Developing countries find it politically easier to argue, that all should be treated the same, except for least developed countries, although their capacities, and need for assistance differ vastly. Industrial countries are expected to provide special, and differential treatment, but in practice, their commitments on market access, preferential treatment, and technical assistance, are not enforceable. Leaving it up to the industrial countries to decide which developing countries get preferential treatment, invites extraneous considerations in determining who gets how much special treatment. Unless higher-income developing countries accept some type of graduated differentiation in their treatment (beyond that granted the least developed countries), there is little prospect of implementing meaningful, legally enforceable special, and differential treatment favoring all developing countries under the WTO.